Research on solidification behavior of selective laser melted Mg-Y-Sm-Zn-Zr alloy: From molten pool to cubic sample. (September 2021) - Wang, Wenli; Yang, Xin; Wang, Kong Kong; He, Lun
Highlights: The size and mode of the molten pool under different laser powers were determined. The influence of process parameters on grain morphology was studied. The microstructure changes caused by remelting and thermal effects were studied. The disc-shaped second phase (Mg, Zn) 3 (Y, Sm) inside the crystal grain was discovered. Abstract: In this study, Mg-Y-Sm-Zn-Zr alloy was fabricated through the selective laser melting (SLM). An investigation was conducted on the solidification behavior from molten pool to cubic sample. Given the effect of parameters, this study analyzed the effect of the remelting and thermal cycling of the powder layer on the solidification behavior. As indicated from the results, the molten pools were all the keyhole mode, and the c-axis of the magnesium matrix in the cubic sample nearly paralleled to the building direction as impacted by the molten pool of the keyhole mode. The grain size insignificantly decreased with the increase in the laser power, and the grain morphology varied from equiaxed grains to columnar grains, accompanied with the angle between layers ranging from 67° to 0°. Moreover, the remelting and the long-term heat preservation in the SLM significantly impacted the grain morphology, thereby causing the grains to be coarsened at the bottom of the sample. Since the long-term heat preservation of the SLM could be equivalent to artificial aging, considerable randomly distributed disc-shaped (Mg, Zn)3 (Y, Sm) were generated in the grains.